Schools as Sites of Social Reproduction: Student Interactions in Diverse Secondary Schools in Nigeria - Marlana Salmon-Letelier; S. Garnett Russell (Journal on Education in Emergencies)
In this study, we explore intergroup relations and student interactions in eight diverse secondary schools in Nigeria over one academic year. We use mixed methods and a social network analysis of these interactions and relationships to highlight the perspectives of students within a divided society. We analyze data from student interviews we conducted and social network data from our student surveys to explore the ways students exhibit ethnic and religious relations in a school setting. This study finds that Hausa Muslims are the most segregated group within Federal Unity Colleges in Nigeria, driven by the intersection of religion, ethnicity, and language. Religion emerges as a stronger social boundary than ethnicity. Our findings also point to the importance of both academic and nonacademic spaces (such as dormitories, where students can separate into groups) in mediating student interactions. Our work contributes to the discourse in the fields of education, conflict, and peacebuilding and, more broadly, to discussions in comparative education about the role schools play in mitigating or exacerbating intergroup conflict.